A Cultural-Pragmatic Investigation of Tattoos among the Youth in Kampala-Uganda - Akinkurolere, Susan Olajoke; Masereka, David (Agathos, 2019)
It is increasingly becoming a common practice to get people with tattoos, especially the youth, in Uganda today. In the past, tattoos were reserved for special subgroups like seamen (sailors), and motorcycle riders (bikers). However, it is now prevalent in other segments of the population, especially the young people. To many, tattoos are still strange and mysterious. It is, therefore, imperative to investigate perceptions of such an act in order to bring to fore meanings that either justify or invalidate the trend. The study employed both qualitative and quantitative methods in the analysis. It was discovered that tattooing is premised on deep-root cultural meaning and beliefs. This study, therefore, concluded that ancient tattooing was intricately woven around the cultural perception of tattoos among the young people and their underlying reasons for the practice, which is generally accepted, whereas, modern tattooing is a practice that majority of the youth do not seem to embrace, considering it foreign, merely imported and obscene, relating it mostly to negative behaviours or vices in the society.
Keywords: tattoos; culture; fashion; foreign